Writing culture : the poetics and politics of ethnography - Clifford, James; Marcus, George E; Fortun, Kim (Berkeley, Calif : University of California Press, 2010)
Introduction : partial truths / James Clifford ## Fieldwork in common places / Mary Louise Pratt ## Hermes' dilemma : the masking of subversion in ethnographic description / Vincent Crapanzano ## From the door of his tent : the fieldworker and the inquisitor / Renato Rosaldo ## On ethnographic allegory / James Clifford ## Post-modern ethnography : from document of the occult to occult document / Stephen A. Tyler ## The concept of cultural translation in British social anthropology / Talal Asad ## Contemporary problems of ethnography in the modern world system / George E. Marcus ## Ethnicity and the post-modern arts of memory / Michael M.J. Fischer ## Representations are social facts : modernity and post-modernity in anthropology / Paul Rabinow ## Afterword : ethnographic writing and anthropological careers / George E. Marcus.
Originally published: c1986. With new foreword. Publication date from publisher's website. "A School of American Research advanced seminar."
boek